Mathematical Modeling and Designing PID Controller for a Quadrotor and Optimize its Step Response by Genetic Algorithm - S. Mohammadali Zanjani; Sayed Mohammad Kargar; Sayed Mohammad Ali Zanjani (Majlesi Journal of Electrical Engineering)
In order to analyze the mathematical modeling and PID controller performance of a quadrotor, this paper firstly, describes the quadrotor flight dynamics according to âNewton-Euler lawsâ, then equations of motion linearized and transfer functions for 6 degree of freedom obtained in state space domain. Classic PID controller based on âZiegler-Nichols methodâ is designed and implemented on system. In order to have better performance, Genetic Algorithm based on step response optimization, is used to optimize PID controller performance and compared with classic method. Finally, step responses comparison for each transfer functions, showed that Genetic Algorithm with PID control synthesis presents better efficiency than the classic PID controller.